Mesocosms and the Organization of Interior Space in Early Ireland. (2015) - Sayers, William
Abstract : In early medieval Ireland, the cosmos was conceived as tripartite, composed of the heavens, earth's surface, and underearth and undersea. Harmonious relations with cosmic forces were assured by just royal rule. Crossing this vertical coordinate, which also had implications for the human hierarchies of rank and function, were the manifold phenomena as known to human life. This external reality was mentally organized as a vast set of homologies, the recognition and maintenance of which contributed to the prosperity and fertility of the kingdom. The literate record displays multiple taxonomies and categories, often expressed in numerical values. Among these are the pentad and, in spatial terms, the quincunx. This fivefoldness and the order it represented were recognized and replicated on a variety of scales: the five provinces of Ireland, the family farm and its neighbors, the house and its outbuildings. Also implicated as mesocosms were the interior arrangements of royal banquet halls, hostels for kings on circuit and other travelers, and law courts. The quincuncial organization of interior space reflects and promotes macrocosmic order but in the great corpus of literate works is the setting for disruptive human dynamics — the stuff of story — often associated with themes of the heroic life and royal rule. This conception of interior space was elaborated in the pagan period and, in formal terms, was readily accommodated in subsequent Christian centuries, with new hierarchies and the perdurable conception of the kingship as stabilizing factors.